Sleeping Beauty, the one who took the really long nap - Mass, Wendy, 1967- (New York : Scholastic, 2012)
In alternating chapters, Princess Rose, a.k.a. Sleeping Beauty, and the Prince who awakens her from her deep enchanted sleep both share their stories of how they grew up, fell in love, and solved the problem of how to be together.
Reprint. Originally published: 2006
Keywords: Princesses -- Fiction; Princes -- Fiction; Fairy tales